Prevalence and Associated Factors of Menstruation Pattern Among Schools Adolescents - Prasai, Meera; Upadhyay, Hari Prasad; Panthi, Srijana; Khadka, Kamal; Kuwar, Roshan (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Menstruation, also known as a period, is a natural process that occurs in the female body as a part of the menstrual cycle. The menstrual cycle is the monthly hormonal cycle that prepares the female body for pregnancy. The objective of this research is to find the prevalence and associated factors of menstruation pattern among schools adolescents. Methods A descriptive cross sectional study was conducted among 355 adolescent girls of (10-19 years) in five boarding and government school of Bharatpur municipality, Chitwan. Self- structure questionnaire was then distributed to those students who had already attended their menstruation. Data was entered and analyse by using descriptive and inferential statistical tools in SPSS 20. P-value <0.05 were considered as statistically significant. Results The mean±SD of age was found 14.60±1.54 years. In 63.9% (With 95 %CI 58.9% to 68.9%) students had irregular menstruation cycle. Likewise18.87% students had Oligomenorrhoea, 17.18% had Polymenorrhoea and 11.3% students had menorrhagia. Family history of students was found as statistically significant with menstruation problem (p-value<0.05). Conclusions Dysmenorrhea, Irregularities in menstruations cycle and Pre menstruation symptoms was found to be major problems in adolescents girls.